Gender Based Behaviour and Differences - Relevant to Online Shopping: A Literature Review Study - Dr. A. V. More, (International Journal of Management Studies (IJMS), 2023)
Purpose: Commonly the marketing companies follow different marketing strategies for female and males. Though there may be existence of different elements like interest or expertise for genders. Gender study is far away than these obvious distinguish elements. It is, trying to understand more basic distinctions like skills, attention or processing and revealing when and how these impact behaviour. Getting insight in the gender differences is vital for researchers for not only marketing activities but also for understanding psychological aspect of consumers and buyers for getting complete benefits of advertising and marketing activities and understanding consumer behaviour. Researchers in consumer psychology have placed very low attention towards the study of gender differences, though these differences are vital in understanding about consumer behaviour. Methodology: This is a literature review based study providing an overview of the gender based behaviour and differences and online shopping behaviour, completed on the basis of study of literature relevant with the topic. Findings: Literature proved that there are different roles played by both genders of females and males like women generally give value to interdependence and inclusiveness, on the other men on independence and instrumentality. Men may promote and support self-benefitting promotional campaigns, spend higher money for enhancing stature while shopping with other peoples, support well-structured online shopping and cope or try to being away from effects of negative emotions. On the other women more support equitable distribution of resources, show attention towards appeals for help of others and for effect of their actions etc., have preference about socially and sensible environment of traditional shopping. Implications: The understanding about the differences of gender will be grown and can be further studied for finding solutions and eradicating strategies of gender differences are developed with the help of integration of the findings of study. For getting advantages of consumer research, it is very important to be in detail about the understanding of cognitive mechanism underlying responses of genders for putting light on aspects of cognitive processing of genders. This will help in further studies for fulfilling the need of theory, which will be putting light fully on spectre of effective outcome (i.e. costs and benefits) of response and processing pattern of both gender also forecasting when which kind of these outcomes will take place. Originality: This literature review based study providing an overview of the gender based behaviour and differences and online shopping behaviour on the basis of study of relevant literature is an original work of author, and all the references are duly cited.